Thyroglobulin levels and thyroglobulin/thyrotropin ratio could predict the success of the ablative/therapeutic 131I in the differentiated thyroid cancers - Trevizam, Paula Grasiele Carvalho [UNESP]; Tagliarini, José Vicente [UNESP]; Castilho, Emanuel Celice [UNESP]; de Alencar Marques, Mariângela [UNESP]; Kiy, Yoshio [UNESP]; da Silva Mazeto, Gláucia Maria Ferreira [UNESP] (Taylor & Francis, 2017)
Background: Stimulated thyroglobulin (STg) levels in patients with differentiated thyroid carcinomas (DTCs) after total thyroidectomy (TT) and before radioactive iodine (131I) ablation/therapy (RIT) are predictive of therapeutic success but can be influenced by the thyroid-stimulating hormone (TSH) level. Objectives: This study compared the reliability of the STg/TSH ratio and STg measurement in predicting the success of RIT. Methods: Sixty-three DTC patients submitted to TT were assessed retrospectively to compare the ability of STg level and the STg/TSH ratio to predict successful RIT. Results: In this study 48 (76.2%) patients had successful RIT. The successful and unsuccessful groups received different 131I doses and had different STg levels and STg/TSH ratios. The STg and STg/TSH ratio cutoff values that predicted successful RIT were 4.41 ng/mL (sensitivity of 86.7% and specificity of 77%) and 0.093 (sensitivity of 80% and specificity of 79.2%), respectively. Age, STg level, STg/TSH ratio, and 131I dose were associated with successful RIT, but after multivariate analysis only STg remained associated (p < 0.05). Conclusion: In conclusion, our data suggest that the STg/TSH ratio and measurement of STg are equally reliable in predicting successful RIT in DTC patients.
Keywords: Biological markers; prognosis; thyroglobulin; thyroid neoplasms; thyrotropin